A systematic review of transanal total mesorectal excision: is this the future of rectal cancer surgery?. (January 2016) - Simillis, C.; Hompes, R.; Penna, M.; Rasheed, S.; Tekkis, P. P.
Abstract: Aim: The surgical technique used for transanal total mesorectal excision (TaTME) was reviewed including the oncological quality of resection and the peri‐operative outcome. Method: A literature search of MEDLINE, Embase, Science Citation Index Expanded and Cochrane was performed in order to identify studies reporting on TaTME. Results: Thirty‐six studies (eight case reports, 24 case series and four comparative studies) were identified, reporting 510 patients who underwent TaTME. The mean age ranged from 43 to 80 years and the mean body mass index from 21.7 to 31.8 kg/m 2 . The mean distance of the tumour from the anal verge ranged from 4 to 9.7 cm. The mean operation time ranged from 143 to 450 min and mean operative blood loss from 22 to 225 ml. The ratio of hand‐sewn coloanal to stapled anastomoses performed was 2:1. One death was reported and the peri‐operative morbidity rate was 35%. The anastomotic leakage rate was 6.1% and the reoperation rate was 3.7%. The mean hospital stay ranged from 4.3 to 16.6 days. The mesorectal excision was described as complete in 88% cases, nearly complete in 6% and incomplete in 6%. The circumferential resection margin was negative in 95% of cases and the distal resection margin was negative in 99.7%. Conclusion: TaTME is a feasible and reproducible technique, with good quality of oncological resection. Standardization of the technique is required with formal training. Clear indications for this procedure need to be defined and its safety further assessed in future trials.